Excessive Atrial Ectopic Activity Worsens Prognosis and Predicts the Type of Major Adverse Cardiac Events in Patients With Frequent Premature Ventricular Contractions - Parreira, Leonor (Cardiol Res, 2019)
BACKGROUND: The aim of the study was to evaluate the impact of premature atrial contractions (PACs) burden, and the presence of non-sustained ventricular tachycardia (NSVT) on prognosis and type of major adverse cardiovascular events in patients with frequent premature ventricular contractions (PVCs). METHODS: We retrospectively studied 285 consecutive patients with frequent PVCs defined as PVC count equal or higher than 1% of total beats assessed with 24-h Holter recording. Patients with atrial fibrillation (AF) were excluded. We evaluated the impact of PAC burden and the presence of NSVT on the primary end points of all-cause mortality, stroke and new-onset AF, and secondary end points; arrhythmic end point (arrhythmic death or hospitalizations for ventricular arrhythmias) or heart failure (HF)-related end point (death or hospitalizations due to HF). RESULTS: The PAC number showed an adjusted hazard ratio (HR) (95% confidence interval (CI), P value) of 1.077 (1.014 - 1.145, P = 0.017) for all-cause mortality, 1.250 (1.080 - 1.447, P = 0.003) for stroke, 1.090 (1.006 - 1.181, P = 0.036) for new-onset AF and 1.376 (1.128 - 1.679, P = 0.002) for the HF end point. The presence of NSVT showed an adjusted HR (95% CI) of 3.644 (1.147 - 11.57, P = 0.028) for the arrhythmic end point. CONCLUSIONS: In patients with frequent PVCs a high PAC count was independently associated with increased mortality, higher rate of AF, stroke and HF adverse events, but not with arrhythmic adverse events. The presence of NSVT was independently associated with increased arrhythmic adverse events, but not with overall mortality, AF, stroke or HF events.